EFEKTIVITAS STRATEGI EXAMPLES NONEXAMPLES DALAM MENINGKATKAN KEMAMPUAN MENULIS SURAT DINAS SISWA KELAS VIII SMP NEGERI 11 KOTA MAKASSAR - Supriadi, S.Pd., M.Pd; Jayanti Sampara (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2018)
Abctract: Abstract: Effectiveness of Examples Non Examples Strategies in Improving theWriting Ability of Class VIII SMP II Service Letters in Makassar State. No result found for Thisstudy aims to examine the effectiveness of applying Nonexamples Examples strategies to improve theability to write official letters for eighth grade students of SMP Negeri 11 Kota Makassar and to examinethe differences in the effectiveness of student learning outcomes by using Nonexamples Examples withconventional models. The type of research used uses a quantitative approach to the method ofexpansion. The research variable consists of two namely the application of Nonexamples Examplesstrategy method as the independent variable X and learning to write official letters as the dependentvariable Y. The research design used in this research is experimental research using quasi-experimentalmethod with the initial test design and the final test of the control group and experimental group withrandom samples Therandomized pretest-posttest control design. The results of this study indicate thatlearning example non example is effective applied in learning to write official service this is based onthe results of the calculation of the significance test which shows that the value of t counts is 51.015 ttable value 2.021.This indicates that the proposed research hypothesis is accepted.